Near infrared activation of an anticancer PtIV complex by Tm-doped upconversion nanoparticles. Issue 11 (23rd December 2014) - Ruggiero, Emmanuel; Hernández-Gil, Javier; Mareque-Rivas, Juan C.; Salassa, Luca
Abstract : The Pt IV complex cis, cis, trans -[Pt(NH3 )2 (Cl)2 (O2 CCH2 CH2 CO2 H)2 ] is photoactivated by near infrared light (980 nm) using NaYF4 :Yb 3+ /Tm 3+ @NaYF4 core–shell upconversion nanoparticles. Abstract : The Pt IV complex cis, cis, trans -[Pt(NH3 )2 (Cl)2 (O2 CCH2 CH2 CO2 H)2 ] is photoactivated by near infrared light (980 nm) using NaYF4 :Yb 3+ /Tm 3+ @NaYF4 core–shell upconversion nanoparticles. Coupling of this cisplatin precursor with the biocompatible PEGylated phospholipid DSPE-PEG(2000)-NH2 affords a valuable approach to decorate the surface of the nanoparticles, providing novel photoactivatable nanomaterials capable of releasing Pt II species upon NIR light excitation.